Egg Production, Egg Quality, and Fatty Acid Profile of Indonesian Local Ducks Fed with Turmeric, Curcuma, and Probiotic Supplementation - Ismoyowati, I.; Indrasanti, D.; Ratriyanto, A.; Sumiati (Tropical Animal Science Journal, 2022)
Indonesian local ducks are commonly raised for egg production purposes. However, the performances of these ducks are still variable and must be improved. This study investigated the effects of turmeric, curcuma, and probiotic supplementations on the egg production and quality of Indonesian local ducks, emphasizing the eggs’ fatty acid profile. Two hundred female local ducks aged 16 weeks were randomly allotted to four dietary treatments with five replicates of 10 birds. The ducks were fed a corn and rice bran-based diet containing different supplements, i.e., a diet without supplementation as the control diet, a diet supplemented with turmeric at the level of 4%, a diet supplemented with curcuma at the level of 4%, and a diet supplemented with starbio probiotics at the level of 2%. The measured data were analyzed using analysis of variance using the 13 Systat program and continued with Duncan’s Multiple Range Test. Turmeric supplementation increased egg production compared with the control, and the duck fed probiotics consumed more feed than the control. Curcuma supplementation generated the lowest feed consumption, egg production, and physical egg quality than the other treatments (p